Meaning-based Translation Using A Semantic Analyser To Resolve Word Sense Disambiguation - Mohamed Azzedine (Al-Lisaniyyat, 2013)
This paper describes a meaning-based approach for automatic translation. It is based on semantic analyser and lexica-semantic dictionary. The approach works at clause level and focus on universal grammar. Predicate and arguments are the nucleus and the periphery ( number of arguments or valence). Topic/Comment/Tail are the unit of communication. They are called Clause at syntactic level and Proposition at semantic level_ The ternary structure is universal and present at different level of the most of human languages.